External beam radiotherapy and radical prostatectomy are associated with better survival in Asian prostate cancer patients. (22nd September 2021) - Würnschimmel, Christoph; Wenzel, Mike; Chierigo, Francesco; Flammia, Rocco Simone; Tian, Zhe; Saad, Fred; Briganti, Alberto; Shariat, Shahrokh F; Suardi, Nazareno; Terrone, Carlo; Gallucci, Michele; Chun, Felix KH; et al.
Abstract : Objectives: To test the effect of race/ethnicity on cancer‐specific mortality after radical prostatectomy or external beam radiotherapy in localized prostate cancer patients. Methods: In the Surveillance, Epidemiology and End Results database 2004–2016, we identified intermediate‐risk and high‐risk white ( n  = 151 632), Asian ( n  = 11 189), Hispanic/Latino ( n  = 20 077) and African American ( n  = 32 550) localized prostate cancer patients, treated with external beam radiotherapy or radical prostatectomy. Race/ethnicity‐stratified cancer‐specific mortality analyses relied on competing risks regression, after propensity score matching for patient and cancer characteristics. Results: Compared with white patients, Asian intermediate‐ and high‐risk external beam radiotherapy patients showed lower cancer‐specific mortality (hazard ratio 0.58 and 0.70, respectively, both P  ≤ 0.02). Additionally, Asian high‐risk radical prostatectomy patients also showed lower cancer‐specific mortality than white patients (hazard ratio 0.72, P  = 0.04), but not Asian intermediate‐risk radical prostatectomy patients ( P  = 0.08). Conversely, compared with white patients, African American intermediate‐risk radical prostatectomy patients showed higher cancer‐specific mortality (hazard ratio 1.36, P  = 0.01), but not African American high‐risk radical prostatectomy or intermediate‐ and high‐risk external beam radiotherapy patients (all P  ≥ 0.2). Finally, compared with white people, no cancer‐specific mortality differences were recorded for Hispanic/Latino patients after external beam radiotherapy or radical prostatectomy, in both risk levels ( P  ≥ 0.2). Conclusions: Relative to white patients, an important cancer‐specific mortality advantage applies to intermediate‐risk and high‐risk Asian prostate cancer patients treated with external beam radiotherapy, and to high‐risk Asian patients treated with radical prostatectomy. These observations should be considered in pretreatment risk stratification and decision‐making.